2020
DOI: 10.3390/toxics8010019
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Toxicity: Connecting the Environment and Gut Microbiome-Associated Diseases

Abstract: The human gut microbiome can be easily disturbed upon exposure to a range of toxic environmental agents. Environmentally induced perturbation in the gut microbiome is strongly associated with human disease risk. Functional gut microbiome alterations that may adversely influence human health is an increasingly appreciated mechanism by which environmental chemicals exert their toxic effects. In this review, we define the functional damage driven by environmental exposure in the gut microbiome as gut microbiome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 128 publications
(176 reference statements)
0
53
0
Order By: Relevance
“…A microbiome is the community of microorganisms in a specified location (Bäckhed et al, 2005) and the microbiomes of vertebrates have myriad effects on their hosts, from digestion (Oliphant and Allen-Vercoe, 2019) and behavior (Borre et al, 2014) to lifespan (Smith et al, 2017) and brain development (Heijtz et al, 2011). Microbiomes are important for the health of hosts and can affect the onset, duration, and severity of diseases, including intestinal diseases, metabolic diseases, obesity, cardiovascular diseases, and others (Kinross et al, 2011;Nicholson et al, 2012;Tu et al, 2020). Most knowledge of vertebrate-associated microbiomes derives from mammalian hosts (Bleich and Fox, 2015;Colston and Jackson, 2016;Davenport et al, 2017;Sharpton, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A microbiome is the community of microorganisms in a specified location (Bäckhed et al, 2005) and the microbiomes of vertebrates have myriad effects on their hosts, from digestion (Oliphant and Allen-Vercoe, 2019) and behavior (Borre et al, 2014) to lifespan (Smith et al, 2017) and brain development (Heijtz et al, 2011). Microbiomes are important for the health of hosts and can affect the onset, duration, and severity of diseases, including intestinal diseases, metabolic diseases, obesity, cardiovascular diseases, and others (Kinross et al, 2011;Nicholson et al, 2012;Tu et al, 2020). Most knowledge of vertebrate-associated microbiomes derives from mammalian hosts (Bleich and Fox, 2015;Colston and Jackson, 2016;Davenport et al, 2017;Sharpton, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco‐related diseases, including cardiovascular disease, Crohn's disease, and cancer, are increasing; however, the role or contribution of THS in these diseases remains largely unknown. Environmental exposures are recognized as important factors that can influence the abundance of specific microbes, which subsequently can act as risk factors for chronic diseases (Colquhoun et al, 2020; Tu et al, 2020). Therefore, the adverse health effects of tobacco smoke including THS may be at least in part mediated by modulating the human gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Yet studies show that early‐life environmental exposures have persistent effects on microbiome composition and function (Lozupone et al, 2012; Snijders et al, 2016). In recent years, evidence has emerged that exposure to toxic environmental chemicals leads to adverse health effects that are mediated through altering the gut microbiome (Colquhoun et al, 2020; Khan & Wang, 2019; Sbihi et al, 2019; Tsiaoussis et al, 2019; Tu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that exposure to xenobiotics such as antibiotics, heavy metals and artificial sweeteners induces gut microbiome toxicity. 53,54,55 Although many studies report on how antibiotic treatment alters gut microbiota, the effect on the gastric microflora is not widely reported.…”
Section: Dysbiosis (Microbial Imbalance) and Associated Diseasesmentioning
confidence: 99%